Related parts from the C13 - Ballesteros Grijalva, Mónica (Universidad de Sonora, 2016)
The concept of related parties also defines how the disclosure of the information is made, the regulation of disclosure of related parties indicating the minimum requirements that must be met to carry it out properly addition, the order logical that must be followed at the time of disclosure, and not by those having a relationship of related parties, is considered as such and others who are not related parties.